Incorporating Internet-Based Application in Teaching and Assessing English for Agriculture Students - Rahmawati Upa; Sri Damayanti (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2021)
Nowadays, teaching using Internet-Based Application becomes an engagement for English as a foreign language (EFL) teacher. Therefore in this research, the researchers are trying to incorporate two internet-based applications (Padlet and Wordwall) to teach English for Agriculture students to identify how these Internet-Based Applications are incorporated and how the students’ responses to the implementation of these. The sample of the research is 20 Agriculture study program students from the fifth semester. The instrument used to gather the data are observation and questionnaires. The questionnaires divided into two, the first is one dealing with the use of Padlet which consisted of 14 statements which divided into three indicators, they’re 1) the ease of use Padlet, 2) students’ understanding material on using Padlet, and 3) Padlet display. The second one is dealing with the use of Wordwall which consist of 6 statements. The result of this research reveals that Padlet was used by the lecturer in the teaching process. It was started by designing some teaching materials and sent it to the Padlet room and gave instruction to the students on what to do dealing with the teaching material. Brainstorming in the beginning and reflection at the end of each meeting were also implemented. Meanwhile Wordwall was used to assess students vocabulary by sending it’s link to Padlet room so the students could access it. Referring to the students’ response, they have very positive response on the use of Padlet as a learning media and Wordwall as formative assessment tool. In one case, it is evidently that students have different response on the use of Padlet with the reality happened during the teaching and learning process.